Pelatihan Pengolahan Limbah Kertas Menjadi Kertas Daur Ulang Bernilai Jual - Ikhwana, Hablil; Ekawati, Yuni Andri (Jurnal Pengabdian Masyarakat Inovasi, 2024)
Paper waste is a crucial environmental issue due to its increasing volume alongside high domestic and office activities. This community service aims to educate and train PKK women in Bane Village, North Siantar District, in processing paper waste into recycled paper with economic value. The method used in this activity consists of theoretical counseling using presentation media and direct practical training (demonstration and practice). The processing stages include pulping, mixing adhesives, and the printing and drying process. The results of the activity showed a significant increase in environmental awareness and technical skills among participants. The PKK women successfully produced aesthetic recycled paper using simple household equipment without requiring large capital. The conclusion of this service is that paper recycling training is effective in changing public perception of waste into creative economic opportunities. Future recommendations include continuous assistance in product packaging and marketing aspects to enhance the economic independence of the PKK group.